THE POLITICS AND ECONOMICS OF PENSION PRIVATIZATION IN LATIN AMERICA. - Madrid, Raul (Latin American Research Review, 2002)
This research note seeks to explain why a large number of Latin American countries have privatized their pension systems in recent years. It argues that the privatization schemes are a response to the severe capital shortages that have plagued their countries intermittently in recent years rather than to the financial problems facing some of the pension systems. The likelihood of pension privatization, I argue, is determined in large part by the vulnerability of countries to capital shortages as well as the influence wielded by international financial institutions, especially the World Bank. Whether such reforms are politically feasible, however, depends largely on the strength of organized labor and the president's degree of control over the legislature. A statistical examination of recent pension policy in Latin America provides support for most of these arguments.